2014
DOI: 10.1016/j.ypmed.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of school meals before and after implementation of nutrition recommendations in five school districts across two U.S. counties

Abstract: Nutrition interventions can have broad reach through changes in menu offerings to school-aged children and adolescents. However, further research is needed to examine how these changes affect student food selection and consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 9 publications
1
32
1
1
Order By: Relevance
“…Our qualitative findings are consistent with and complement several recent quantitative studies related to school meal reform. Studies have reported that overall, student selection and consumption of fruits and vegetables increased after implementation of the new meal standards . In addition, FSDs' references to the importance of the “bigger puzzle” in children's health are consistent with a body of literature that identifies schools as one component of a complex and dynamic system influencing children's health .…”
Section: Discussionmentioning
confidence: 57%
“…Our qualitative findings are consistent with and complement several recent quantitative studies related to school meal reform. Studies have reported that overall, student selection and consumption of fruits and vegetables increased after implementation of the new meal standards . In addition, FSDs' references to the importance of the “bigger puzzle” in children's health are consistent with a body of literature that identifies schools as one component of a complex and dynamic system influencing children's health .…”
Section: Discussionmentioning
confidence: 57%
“…In the present study the energy content available from reference portions of school meals was on average lower than described in other studies outside of the Nordic region . For example, in a Spanish study, the median energy content of available school meals for 4‐ to 12‐year‐olds was 706 kcal and said to be adequate according to recommendations for the Spanish population for different age groups .…”
Section: Discussionmentioning
confidence: 61%
“…While the results of present study indicate a need for standardization and possibly need of larger portions to secure availability, others have tried to reduce the energy content of school meals. For example, an intervention study from the United States brought a reduction in energy content from 715 kcal to 681 kcal in offered lunch, with portions after intervention being closer to recommendations . The mean energy content after the intervention was nonetheless still higher than seen in present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a case example, to assist local school districts to meet the latest nutrition standards of the United States Department of Agriculture's National Lunch and Breakfast Programs, the Los Angeles County Department of Public Health (DPH) partnered with the UCLA Fielding School of Public Health during the 2011–2012 school year to assist the Los Angeles Unified School District in restructuring their meal programs, including menu changes and food environment modifications (i.e., redesign of the location and presentation of foods) . DPH and UCLA used a collaborative laboratory approach, providing evaluation support to assess program improvements; evaluation methods included nutritional analysis to verify desired changes in nutrient limits (e.g., sodium, calories, sugar, and fat) in the school cafeterias and documentation of food waste via reviews of food production records and a series of plate waste studies at four randomly selected middle schools . In an ongoing project, DPH is conducting a study to better understand the effects of accompanying behavioral economics strategies in promoting healthy eating—in the same school cafeterias where menu changes had occurred.…”
Section: Challenges and Identified Solutions For Advancing DII Sciencmentioning
confidence: 99%